In consideration of latino children: a sociocultural perspective of literacy skills development using literature circles - Bryant, M.A., Stephanie A. Bryant, M.A. A. (Colombian Applied Linguistics Journal, 2005)
This article, refl ecting a sociocultural perspective and connections to current research, presents a discussion about the importance of engaging Latino children in literature circle discussions using culturally appropriate, meaningful, and relevant childrenʼs literature in classrooms in the United States. In addition, teachers are encouraged to be refl ective practitioners and to consider a “funds of knowledge” perspective by taking time to understand the literacy practices of the families at home and how they may contribute to success in school for Latino children.